Oral daily melatonin supplementation attenuates oxidative stress in testes of men with idiopathic infertility - Riviere, Eugenia (2019)
Melatonin (mel) modulates testicular function acting indirectly through the hypothalamus/pituitary and directly on different gonadal cells. We previously demonstrated that testicular expression of several inflammatory markers was increased in biopsies of infertile patients compared to biopsies of men with normal spermatogenesis. Oral mel intake attenuated testicular inflammation in infertile patients.Because inflammation and oxidative stress are co-dependent pathophysiological processes, and mel is known as a potent antioxidant agent, in this study we evaluated the impact of oral mel supplementation on testicular oxidative state in infertile patients.Testicular biopsies of patients with idiopathic infertility (n=35) and normal histology (n=6) were used. A sub-group of infertile patients (n=11) were under mel supplementation (3 mg single oral daily dose) to treat sleep disorders.Mel concentration was lower in testes of infertile patients compared to gonads of men with normal morphology. Oral daily mel intake in infertile patients restored testicular mel concentration close to control levels (p<0.05). Lipid peroxidation (TBARs assay) as well as the protein expression levels (Western blot) of the antioxidant enzymes superoxide dismutase 1 (SOD1), catalase and peroxiredoxin 1 (Pxr1) were statistically increased in testicular biopsies of infertile patients compared to gonads with normal histology (p<0.05) suggesting that, in pathological conditions, testicular oxidative stress activates the enzymatic defense mechanisms to prevent further injury. An oral daily dose of mel, decreased testicular TBARs generation as well as SOD1 and catalase expression to control levels (p<0.05). No significant differences were found in Pxr1 and glutathione peroxidase 1-2 expression levels between biopsies of infertile patients supplemented or not with mel.In conclusion, these results reveal that oral daily mel intake reduces oxidative stress in testes of patients with idiopathic infertility.